Sistem Informasi Pembuatan Administrasi Kependudukan di Desa Parit Bindu - Damanik, Burhanuddin; Ginting, Devi Andriani; Hutagalung, Dini M.; Ginting, Riah Ukur (Universitas Sari Mutiara Indonesia Medan, 2022)
Information technology is an inseparable part of modern society. Currently, there are many information technologies that make human work easier, especially providing optimization and accelerating human activities. Good information technology is expected to make it easier for people to complete tasks and can replace manual processes with computerized digital processes. The purpose and objective of creating this system is to produce a system that can be used to make it easier for Parit Bindu villagers to submit letters and improve the efficiency of administrative services in Parit Bindu village. The method used in the development of this system is waterfall namely Requirements Analysis and Definition, System and Software Design, Implementation and Unit Testing, Integration and System Testing, and Operation and Maintenance. The Information System for Making Population Administration helps data processing in a more precise, fast, practical and efficient manner. Population data can be stored safely and easily searched by administrators or officers, so that service to the public is faster.